2012
DOI: 10.1111/j.1365-2265.2011.04322.x
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue IL‐8 is increased in normal weight women after menopause and reduced after gastric bypass surgery in obese women

Abstract: Postmenopausal women have an increased inflammatory response in the subcutaneous fat and circulation. Inflammatory markers in adipose tissue decreased significantly after surgery-induced weight loss. This effect may be beneficial for metabolic control and reduced cardiovascular risk after weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Correlative studies show that resistance exercise increases skeletal muscle mRNA expression of IL6 and IL8 [38]. Furthermore, in adipocytes, RYGB surgery has been reported to markedly reduce IL8 expression [39]. Therefore, local IL8 secretion could be more sensitive and an early marker of metabolic changes occurring 6 months after RYGB surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Correlative studies show that resistance exercise increases skeletal muscle mRNA expression of IL6 and IL8 [38]. Furthermore, in adipocytes, RYGB surgery has been reported to markedly reduce IL8 expression [39]. Therefore, local IL8 secretion could be more sensitive and an early marker of metabolic changes occurring 6 months after RYGB surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Although IL-8 is one of the key chemokines that regulate migration and infiltration of neutrophils, expression of IL-8 is upregulated in the AT of obese patients (Alvehus et al. 2012). Interestingly, Neels et al.…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophils are recruited to various tissues through chemokines and adhesion molecules. Although IL-8 is one of the key chemokines that regulate migration and infiltration of neutrophils, expression of IL-8 is upregulated in the AT of obese patients (Alvehus et al 2012). Interestingly, Neels et al (2009) showed that in obese mice deficient in CXCL2, the receptor for IL-8, presented reduced macrophage infiltration in the AT from levels in control obese mice (Neels et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The menopause was characterized by increased body weight (Alvehus et al 2012). First, we investigated the regulatory effect of body weight of PPE or Arg in the OVX mice.…”
Section: Administration With Ppe or Arg Improved Body And Vagina Weigmentioning
confidence: 99%